Depressive symptoms among immigrant and Canadian born mothers of preterm infants at neonatal intensive care discharge: a cross sectional study - Ballantyne Marilyn; Benzies Karen M; Trute Barry (BMC, 2013)
Abstract Background Mothers of preterm infants are considered at higher risk for depressive symptoms, higher than for mothers of healthy term infants. Predictors of depressive symptoms in mothers of preterm infants are not yet well established. Immigrant mothers of term infants have higher prevalence of depressive symptoms than Canadian born mothers but the relative prevalence for immigrant mothers of preterm infants is unknown. This study had two aims: (i) to investigate the prevalence of depressive symptoms in immigrant as compared to Canadian born mothers of preterm infants, and (ii) to determine what factors are associated with depressive symptoms in mothers of preterm infants. Methods This is a multi-site, cross sectional study of mothers whose preterm infants required hospitalization in neonatal intensive care unit (NICU). Consecutive eligible mothers (N = 291) were recruited during the week prior to their infant's NICU discharge. Mothers completed a self-administered questionnaire booklet of validated psychosocial/cultural measures including the Center for Epidemiological Studies Depression Scale (CES-D), Parental Stressor Scale:NICU, General Functioning Subscale of the McMaster Family Assessment Device, Social Support Index, and Vancouver Index of Acculturation; and demographic characteristics questions. Infant characteristics included gestational age, birth weight, sex, singleton/multiple birth, and Score for Neonatal Acute Physiology-II. Results Immigrant mothers (N = 107), when compared to Canadian born mothers (N = 184), reported more depressive symptoms, poorer family functioning, less social support, and less mainstream acculturation. Hierarchical regression for a subsample of 271 mothers indicated that single parent status, high stress, poorer family functioning, and less social support were associated with increased depressive symptoms and accounted for 39% of the variance on the CES-D. Immigrant status did not contribute significantly to the final regression model. Conclusions Immigrant mothers of preterm infants are at increased risk for depressive symptoms. For immigrant and Canadian born mothers of preterm infants hospitalized in NICU and particularly for single mothers, interventions to reduce stress and increase family functioning and social support may reduce depressive symptoms. Given the effects of depression on maternal health and functioning, such an intervention may improve child outcomes.